Response of a mass-spring system subject to Coulomb damping and harmonic base excitation. (1st June 2020) - Riddoch, Daniel J.; Cicirello, Alice; Hills, David A.
Abstract: The periodic response of a mass-spring system is studied and the behaviour described, including the creation of finite dwell periods. A parameter space investigation is conducted and a branch of behaviour with the space is explained. A new solution method is proposed for direct calculation of the steady-state response without calculating a transient phase. A new approach to the display of the steady-state response is given. Finally, the system behaviour near its resonance is explored and new asymptotic solutions are proposed for the response amplitude near resonance. The accuracy of these solutions is then determined by comparison to the true solution.